Dampak Atribut Produk, Virality, dan Rekomendasi terhadap Keputusan Pembelian Produk - Kukuh Judy Handojo; Nugroho Edie Santoso (IPM2KPE, 2022)
Purchase decision in skincare product by consumers at this time influenced by many factors, including product attributes, virality, and recommendation. This research aims to (1) describe the influence of product attribute towards purchase decision in skincare product (2) describe the influence of virality towards purchase decision in skincare product (3) describe the influence of recommendation towards purchase decision in skincare product. This research uses the basic methode of descriptive analytic. This research was held in Lumajang, Jember and Banyuwangi. Research location determinded using purposive sampling and samples determined using judgement sampling with 181 respondents. Technique of collecting data through observation, interviews, and questionnaires. Analysis method done by Structural Equation Models (SEM) with alternative method of Partial Least Sqaure. The results showed that : (1) product atribute is positive towards purchasing decision. (2) virality is positive towards purchasing decision. (3) recommendation has no effect against purchasing decision. Keyword: Product Atribute, Virality, Recommendation, Purchasing Decision, Structural Equation Model (SEM), Partial Least Square